Cooperative Radio Communications for Green Smart Environments. - Cardona, Narcis. (River Publishers, 2016)
This book addresses both the techniques to model, analyse and optimise the radio links and transmission systems in such scenarios, together with the most advanced radio access, resource management and mobile networking technologies.